2019
DOI: 10.5194/gi-8-187-2019
|View full text |Cite
|
Sign up to set email alerts
|

In situ calibration of offsetting magnetometer feedback transients on the Cassiope spacecraft

Abstract: Abstract. We present an in situ calibration process to derive the transient behavior of the offsetting fluxgate magnetometer (MGF) instruments on the Cassiope spacecraft. The dynamic behavior of the MGF changed on orbit following a software update. Characterizing the new instrument dynamics during normal spacecraft operations and then removing the transients was confounded by significant magnetic interference from the reaction wheels used to orient the spacecraft. Special operations were performed where data w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…The first experiment shown highlights the ability of M‐SSA to successfully decompose real magnetometer data into physically meaningful components that can be automatically grouped using the technique described in Section 2.3. Figure 6 illustrates the results of M‐SSA applied to a pair of magnetometer measurements containing previously identified field‐aligned currents and Alfvénic activity (Miles et al., 2019). The inboard and outboard magnetometer measurements are illustrated in Figure 6a.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first experiment shown highlights the ability of M‐SSA to successfully decompose real magnetometer data into physically meaningful components that can be automatically grouped using the technique described in Section 2.3. Figure 6 illustrates the results of M‐SSA applied to a pair of magnetometer measurements containing previously identified field‐aligned currents and Alfvénic activity (Miles et al., 2019). The inboard and outboard magnetometer measurements are illustrated in Figure 6a.…”
Section: Resultsmentioning
confidence: 99%
“…During this time, the CASSIOPE/Swarm-Echo spacecraft crossed a dynamic dual discrete arc aurora. Previous analysis of this event (Miles et al, 2019) demonstrated that, as the spacecraft transits magnetically conjugate to the aurora, it observes in situ magnetic signatures of both a static field-aligned current (with ∼10 to 20 s period) and the nonstationary electrodynamics of reflected and interfering Alfvèn waves (at ∼1 to 10 Hz) associated with the small-scale dynamic features observed in the auroral imaging.…”
Section: Datamentioning
confidence: 89%
See 1 more Smart Citation
“…The use of a single magnetometer requires that spacecraft noise be carefully characterized before launch. Otherwise, a change in spacecraft behavior may require special maneuvers to re-characterize noise signatures in situ (Miles et al, 2019). The use of multiple magnetometers allows for the discovery of noise signals through the comparison of magnetometer data.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the spacecraft Cassiope, a software update changed the behavior of the spacecraft's fluxgate magnetometer (MGF). Special spacecraft maneuvers to decrease the spacecraft's noise signature were required in order to recalibrate the MGF (Miles et al, 2019). Algorithms to autonomously identify spacecraft noise would allow Cassiopie to do in situ MGF calibration without special spacecraft maneuvers.…”
mentioning
confidence: 99%